2014
DOI: 10.1038/ncomms4571
|View full text |Cite
|
Sign up to set email alerts
|

An alternate binding site for PPARγ ligands

Abstract: PPARγ is a target for insulin sensitizing drugs such as glitazones, which improve plasma glucose maintenance in patients with diabetes. Synthetic ligands have been designed to mimic endogenous ligand binding to a canonical ligand-binding pocket to hyperactivate PPARγ. Here we reveal that synthetic PPARγ ligands also bind to an alternate site, leading to unique receptor conformational changes that impact coregulator binding, transactivation and target gene expression. Using structure-function studies we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
216
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(227 citation statements)
references
References 65 publications
7
216
0
4
Order By: Relevance
“…One is CLBP with the predicted docking score of −34.72 kJ/mol, and the other is a second binding site with a docking score of −28.03 kJ/mol, indicating BVC occupied the CLBP with higher binding affinity. The second binding site for BVC was consistent with the alternative binding site (ABS), which was composed of H2′, Ω loop, H3 and β sheets [33]. In addition, if one BVC was docked to CLBP first (Fig.…”
Section: Lc 2 7 a 4 F G F 2 1 A D Ip O Q A C A C B P P A R -A C A D Mmentioning
confidence: 59%
See 2 more Smart Citations
“…One is CLBP with the predicted docking score of −34.72 kJ/mol, and the other is a second binding site with a docking score of −28.03 kJ/mol, indicating BVC occupied the CLBP with higher binding affinity. The second binding site for BVC was consistent with the alternative binding site (ABS), which was composed of H2′, Ω loop, H3 and β sheets [33]. In addition, if one BVC was docked to CLBP first (Fig.…”
Section: Lc 2 7 a 4 F G F 2 1 A D Ip O Q A C A C B P P A R -A C A D Mmentioning
confidence: 59%
“…PPAR senses ligands through ligandbinding sites in the LBD [43,44]. The PPAR-γ-LBD has shown two binding sites, CLBP and ABS; synthetic PPAR ligands are designed to bind to CLBP by mimicking endogenous ligands [33]. GW9662, a PPAR covalent antagonist, can compete for the CLBP of synthetic ligands to PPAR and block binding to CLBP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to a plethora of studies in the field of enzymology, where the phenomenon of allostery was first described (Monod et al, 1963(Monod et al, , 1965Koshland et al, 1966;Changeux, 2013), allosteric modulators have now been identified for all receptor superfamilies, including ligand-gated ion channels (Olsen et al, 2004;Taly et al, 2009;Traynelis et al, 2010), voltage-gated ion channels (Spedding et al, 1995;Catterall et al, 2007), nuclear hormone receptors (Estebanez-Perpina et al, 2007;Hughes et al, 2014), receptor tyrosine kinases (Bono et al, 2013;De Smet et al, 2014), and GPCRs. As a consequence, there exists a large body of literature in which the definition of the term "allosteric" and the description/classification of allosteric ligands can be quite varied and, in many instances, confusing (Colquhoun, 1998;Fenton, 2008;Nussinov and Tsai, 2013).…”
Section: Classification Of Allosteric Modulatorsmentioning
confidence: 99%
“…For example, the androgen receptor possesses a unique binding surface, termed BF-3, that recognizes small molecules such as 3,3,5-triiodothyroacetic acid to allosterically modulate the binding of coactivators to the adjacent AF-2 region (Estebanez-Perpina et al, 2007b). Most recently, a novel allosteric ligand binding site was identified on PPARg that, when bound by small molecules, engendered a unique pharmacological profile of regulation of the receptor (Hughes et al, 2014). This suggests that the design of allosteric ligands for NHRs may be primed to develop as a field, akin to other classes of receptor modulators over the past decade.…”
Section: Nuclear Hormone Receptorsmentioning
confidence: 99%